FACTORS INFLUENCING/AFFECTING PURCHASE BEHAVIOUR OF CONSUMERS TOWARDS ORGANIC FOOD PRODUCTS (International Journal of Engineering Sciences & Management Research, 2017)
This paper measures the effect of several factors on the behaviour of consumers who purchase organic food products in the Vellore district, Tamilnadu. A quantitative survey revealed for a factors influencing /affecting purchasing behaviour of consumers on organic to be influenced by health consciousness, perceived quality, concern over health safety, trust in organic labelling and price premium. The effect of the current economic recession was found to be statistically insignificant on behaviour. Organic food is generally looked upon as an alternative to conventional food for consumers who are concerned about food safety and quality. Despite this, many consumer perceptions about safety and quality are not substantiated by scientific evidence. A detailed questionnaire was prepared and made survey for the sample size of 200 customers and using statistical tools of chi-square, ANOVA, and correlation.